Study of The Role and Function of Agricultural Extension Institutions on Agricultural Development - Hamadal, Rusdi; Umar, Muhammad Agus; Tarwoyo, Tribudi Prihatini (Lumbung Pare Cendekia, 2024)
The role and function of the agricultural extension service for agricultural development which includes services, center of communication, center of institutional development and center of partnership development and the function of extension services as program planning and preparation, provision and dissemination of information, human resource development, administrative structuring and functions evaluation were less optimal. The lack of quantity and quality of agricultural (plantations), extension agents had lack of training along with agricultural (plantations) extension workers, there was a policy of transition from agricultural (plantations) extension workers to food extension workers. Agricultural (plantation) development also seen from economic growth, community welfare, and the increase in plantation production. The decline in production results in several commodities namely cloves, rubber, cocoa and coffee based on data from the statistical center since 2019 to 2022 in Bulukumba regency.